[Back to the fold ; Playing with a chance ; Searching for a home [videorecording] /executive producer, Cheche Lazaro. - Lazaro, Cheche (The Probe Team, 1993)
An investigative report on the transformation of a respected spokesman for the New People's Army. PAGCOR's putting in more casinoes. Includes interviews with the church, moralists and people on PAGCOR's expanded operations. The opening and closure of Hapag Kalinga Restaurant run by former street children.